FORECASTING OF ELECTRICITY CONSUMPTION IN ASSAM BY USING MATHEMATICAL AND TIME SERIES MODELS AND COMPARISON OF THEIR PREDICTIVE PERFORMANCES. (2021) - MAHANTA, NIBEDITA; TALUKDAR, RUMA
No abstract available